Efektivitas Aromaterapi Lavender dan Peppermint Terhadap Skala Nyeri Haid Pada Remaja Putri - Lia Fitria; Anisa Febrianti; Arifah Arifin; Arifatul Hasanah; Dianatul Firdausiyeh (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Adolescent girls will experience changes in the reproductive system marked by menstruation. Menstruation experienced in adolescents is often accompanied by complaints of menstrual pain. Menstrual pain can interfere with daily activities, so it requires treatment to reduce menstrual pain. One way of handling that can be done is with aromatherapy. Lavender and peppermint aromatherapy is a treatment that uses lavender and peppermint essential oils which contain linalool and linalyl acetate which are useful for reducing menstrual pain. The purpose of this study was to determine the effectiveness of lavender aromatherapy with peppermint on the menstrual pain scale in adolescent girls. The research design used was quantitative, quasi-experimental method with a two-group pre-test and post-test design with a sample of 14 respondents, 7 respondents in the lavender aromatherapy group and 7 respondents in the peppermint aromatherapy group. The sampling technique used consecutive sampling. The instrument used is a numerical rating scale (NRS). Data were processed by Wilcoxon test and Mann Whitney test. The results of this study indicate that lavender aromatherapy and lemon aromatherapy are effective in reducing menstrual pain scale with p value 0.001 (p < 0.05). Levender aromatherapy and peppermint aromatherapy were effective in reducing menstrual pain scale, but there was no significant difference in reducing pain scale in both lavender and peppermint therapy groups.